2007
DOI: 10.14507/epaa.v15n16.2007
|View full text |Cite
|
Sign up to set email alerts
|

From policy design to campus: Implementation of a tuition decentralization policy.

Abstract: Citation: Harris, M. S. (2007). From policy design to campus: Implementation of a tuition decentralization policy. Education Policy Analysis Archives, 15(16) AbstractThis study analyzes the implementation of a tuition decentralization policy in North Carolina. Concepts of organizational culture served as a guiding framework for an interpretive analysis. Qualitative case study data for the research was collected from interviews with key policy makers within the University of North Carolina as well as an extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…El no reconocimiento de los actores desde el diseño de la política y, adicional a esto, la no adaptación de las líneas de política a sus intereses o necesidades reales, genera resultados como los que se muestran en esta investigación, y es la dilución de grandes planes en acciones desarticuladas y poco eficaces. Incluir la voz de los actores en los análisis de política proporciona una imagen más completa del proceso, de allí la necesidad de contar con datos cualitativos que permitan profundizar en los actores y sus creencias (Harris, 2007).…”
Section: Discussionunclassified
“…El no reconocimiento de los actores desde el diseño de la política y, adicional a esto, la no adaptación de las líneas de política a sus intereses o necesidades reales, genera resultados como los que se muestran en esta investigación, y es la dilución de grandes planes en acciones desarticuladas y poco eficaces. Incluir la voz de los actores en los análisis de política proporciona una imagen más completa del proceso, de allí la necesidad de contar con datos cualitativos que permitan profundizar en los actores y sus creencias (Harris, 2007).…”
Section: Discussionunclassified
“…In North Carolina, policy makers implemented decentralized tuition policies that allowed institutions to set college prices based on campus mission and values (Harris, 2007). An intention of the policy was to help students make a more informed decision about the college that they decided to attend by evaluating costs and purpose at the same time.…”
Section: Global Journal Of Educational Studiesmentioning
confidence: 99%
“…Even with the growth of the literature, research on the influence of institutional culture on the results of policy implementation has not been growing steadily and continuously (Harris, 2007). Harris (2007) studied a tuition decentralization policy implemented in North Carolina and found that institutional values and culture influence how policy implementation is enacted. This is significant to understanding what was at stake in the China textbook adoption.…”
Section: Policy Implementation Influenced By Values and Culturementioning
confidence: 99%
“…The top-down model refers to a policy decision that is made by a formal authority at a higher level of power and minimizes the power at the level of implementation (Harris, 2007). The bottom-up model refers to the fact that participants at the implementation level were directly and actively involved with creating and carrying out the policy (Harris, 2007).…”
Section: Policy Implementation Influenced By Values and Culturementioning
confidence: 99%
See 1 more Smart Citation